Pembelajaran Lingkungan melalui Pengembangan Subjek Spesifik Pedagogi Berbasis Problem Based Learning untuk Menguatkan Literasi Lingkungan Siswa Kelas X MIA SMA - Windi Mega Widianingsih; Puguh karyanto; Baskoro adi prayitno (Universitas Sebelas Maret, 2017)
The research aims to know about the characteristics, feasibility, and effectiveness of subject specific pedagogy equipment based on PBL to reinforce students environmental literacy in grade X MIA Senior High School. Research conducted by research and development SSP based on PBL. Design of research was using the 3D Model which has been modified from 4D model by Thiagarajan & Stolovitch. The research model consist of define, design and develop, while disseminate phase wasn’t use in this research. The analysis of data consist of needs analysis, validation data analysis, limited trial test analysis, subject test analysis, and environmental literacy. Environmental literacy analysis used the normality test, homogenity test, and non paired samples ttest. This research give three kinds of result. First, the characteristic of SSP equipment based on PBL was integrated with New Ecological Paradigm dimention and was developed by PBL steps. Second, feasibility based on validation result from expert judgments and user showed that 92,5% in RPP (valid), 87,97 % in module (valid), 88,33 % in LKS (valid) and 90 % in evaluation question (valid). The result of limited trial test from student and teacher showed that 91,15 % in modul (valid) and 87,49 in LKS (valid). The result of subject test showed that 91,69% in module (valid) and 89,04% in LKS (valid). SSP equipment based on PBL was valid to use for environmental learned in X MIA class. Third, SSP based on PBL effectively to reinforce environmental literacy consist of knowledge, attitude, and concern aspect. Effectiveness test showed that significance was smaller than α (sig. < 0,05) that meant there was differences between result of student’s environmental literacy with learning used SSP based on PBL and without SSP based on PBL. Keywords